Pengaruh Model Pembelajaran dan Kemampuan Numerik Terhadap Hasil Belajar Permesinan dengan Mengontrol Potensi Keteknikan - Agus Dudung (JTP - Jurnal Teknologi Pendidikan, 2017)
This study aims to examine the effect of learning model and numerical ability on the learning result of machining course by controlling the engineering potential. The method used is quasi experiment with design treatment by level 2 X 2. The sample of research is the students of Mechanical Engineering class A and B using multistage random sampling. Based on the analysis, the results of the study were: the learning result of the students' subjects with problem-based learning is higher than the students with project-based learning after controlling the engineering potential; there is an interaction effect of application of learning model and numerical ability to learning result of machining course; student learning outcomes of students with high numerical skills with problem-based learning, are higher than in the group of students with project-based learning.